2011
DOI: 10.1007/s00125-011-2203-8
|View full text |Cite
|
Sign up to set email alerts
|

Insulin X10 revisited: a super-mitogenic insulin analogue

Abstract: The molecular safety of insulin analogues has received a great deal of attention over the last year. In particular, attention has been directed to the mitogenic properties of insulin analogues as compared with human insulin. Understanding the mechanisms implicated in mediating mitogenic effects of insulin is therefore of particular interest. In this review we detail the story of the rapid-acting insulin analogue known as X10, which was the first insulin analogue in clinical development, but ended up being disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(74 citation statements)
references
References 36 publications
(58 reference statements)
1
72
0
1
Order By: Relevance
“…Prolonged binding of an insulin analog to hIR can result in prolonged activation of the tyrosine kinase domain of hIR, leading to extended tyrosine phosphorylation and downstream signaling (Kurtzhals et al, 2000;Hansen et al, 2011). To gain insight into an insulin agonist/hIR interaction or residence time, a time course of hIR dephosphorylation following a washout of maximally efficacious doses of insulin test samples was measured (Fig.…”
Section: Biological Properties Of Basal Insulin Peglispromentioning
confidence: 99%
“…Prolonged binding of an insulin analog to hIR can result in prolonged activation of the tyrosine kinase domain of hIR, leading to extended tyrosine phosphorylation and downstream signaling (Kurtzhals et al, 2000;Hansen et al, 2011). To gain insight into an insulin agonist/hIR interaction or residence time, a time course of hIR dephosphorylation following a washout of maximally efficacious doses of insulin test samples was measured (Fig.…”
Section: Biological Properties Of Basal Insulin Peglispromentioning
confidence: 99%
“…The first rapid-acting insulin analogue was developed by replacing a histidine residue for the negatively charged aspartic acid at position B10 (insulin X10 or B10Asp; Hansen et al 2011). The applied genetic modification led to disrupting the ability of insulin molecules to self-associate as hexamers.…”
Section: The Common Origin Of Insulin Igfs and Their Receptorsmentioning
confidence: 99%
“…Insulin X10 has been shown to induce enhanced mitogenic effects due to the activation of both the IRs and the IGF1Rs (Milazzo et al 1997). In most studies, its binding affinity for the IR has been found to be 200-400% higher than that of human insulin (Hansen et al 2011). Although it has an identical 'on-rate', it has a much slower 'off-rate' from the IR than human insulin (Drejer et al 1991).…”
Section: The Common Origin Of Insulin Igfs and Their Receptorsmentioning
confidence: 99%
“…In clinical pharmacological studies, insulin degludec exerted a long‐lasting action (>42 h)11, with a flat and stable insulin profile in the glucose‐lowering effect for individual patients12.…”
Section: Introductionmentioning
confidence: 99%